The Role of Nonverbel Communication in Teaching - Kasimov Anvar Bahrom ugli (Zien Journals, 2022)
The main aim of this article was to determine the effect of the teachers’ non-verbal communication on success in teaching using the findings of the studies conducted on the relationship between quality of teaching and the teachers’ use of non-verbal communication and its impact on success in teaching
Keywords: non-verbal communication; teachers; tudent’s achievement-motivation; communication